Spesies Invasif Cagar Biosfer Bromo Tengger Semeru Arjuno: Urgensi Pengaturan Pengendaliannya (RechtJiva, 2025)
Indonesia is a country known as a megabiodiversity country because of the diversity of its natural resources. This results in Indonesia having its own potential and challenges in terms of invasive species. Especially biosphere reserves as a place for ecosystem conservation and the species in them as well as a center for scientific training, monitoring, education, and training. This study aims to identify the urgency and analyze the forms of invasive species control regulations in the Bromo Tengger Semeru Arjuno Biosphere Reserve (CB-BTSA) area by the East Java Provincial Government based on a comparison with invasive species regulations in Vietnam and South Africa. This journal research uses a normative juridical method with statute approach, comparative approach and historical approach. The results of the study indicate that regulations related to invasive species control in the CB-BTSA area are important to be formed immediately because the East Java Provincial Government has not been proactive in controlling the existence of invasive species that threaten the biodiversity of CB-BTSA so that it is necessary to strengthen Indonesia memiliki regulations related to invasive species control in the CB-BTSA area through the preparation of East Java Provincial Regulations.